The impact of hearing loss on cognitive impairment: The mediating role of depressive symptoms and the moderating role of social relationships - Cao, Xia; Liu, Qian; Liu, Jiali; Yang, Bingfang; Zhou, Jiansong (Frontiers in Public Health, 2023)
Background Given the potentially negative effects of hearing loss on mental health and cognitive function, it is critical to gain a better understanding of the mechanisms underlying the link between hearing loss and cognitive impairment. This study aimed to investigate the moderating effects of social relationships, including their components in the role of depressive symptoms as a mediator between hearing loss and cognitive impairment. Methods Cross-sectional analyses were conducted with 8,094 Chinese older adults (aged ≥65 years) from the Chinese Longitudinal Healthy Longevity Survey in 2018. Simple mediation analysis and moderated mediation analysis were conducted to examine the roles of depressive symptoms and social relationships in the association between hearing loss and cognitive impairment. Results There is a significant correlation between hearing loss, depressive symptoms, social relationships, and cognitive function. Depressive symptoms partially mediated the association between hearing loss and cognitive function [standardized regression B-coefficient (B) = −0.114; 95% confidence interval (CI): (−0.158, −0.076)]. Social relationships moderated the effect of hearing loss on cognitive function through both path b (depressive symptoms - cognitive function) [B = 0.021; 95% CI: (0.008, 0.034)], and path c’ (hearing loss-cognitive function) [B = 0.597; 95% CI: (0.463, 0.730)]. Furthermore, social activities and social networks moderated both the direct and indirect effects of moderated mediation. However, there appeared to be no moderated effect of social support for both the direct and indirect paths. Conclusion Social relationships moderated both the direct and indirect effects of depressive symptoms on the association between hearing loss and cognitive impairment. These findings shed light on the mechanisms underlying the relationship between hearing loss and cognitive impairment in Chinese older adults. It might be worthwhile to recommend multidimensional health and social interventions aimed at improving mental health and social inclusion among older adults with hearing loss.